2017
DOI: 10.1208/s12248-017-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Metabolite Identification Studies for the New Synthetic Opioids Acetylfentanyl, Acrylfentanyl, Furanylfentanyl, and 4-Fluoro-Isobutyrylfentanyl

Abstract: New fentanyl analogs have recently emerged as new psychoactive substances and have caused numerous fatalities worldwide. To determine if the new analogs follow the same metabolic pathways elucidated for fentanyl and known fentanyl analogs, we performed in vitro and in vivo metabolite identification studies for acetylfentanyl, acrylfentanyl, 4-fluoro-isobutyrylfentanyl, and furanylfentanyl. All compounds were incubated at 10 μM with pooled human hepatocytes for up to 5 h. For each compound, four or five authent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
145
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(163 citation statements)
references
References 31 publications
(36 reference statements)
15
145
3
Order By: Relevance
“…Multi-donor human hepatocytes have proven to be a useful system to study the metabolism of fentanyls and identified metabolites correlate well with those found in authentic urine samples (Watanabe et al 2017). …”
Section: Introductionmentioning
confidence: 89%
“…Multi-donor human hepatocytes have proven to be a useful system to study the metabolism of fentanyls and identified metabolites correlate well with those found in authentic urine samples (Watanabe et al 2017). …”
Section: Introductionmentioning
confidence: 89%
“…Minor metabolites are also created through various other pathways. For example, despropionylfentanyl is formed by carboxamide hydrolysis, while both hydroxyfentanyl and hydroxynorfentanyl metabolites are hydroxylated at the propionyl moiety (Watanabe et al, 2017). All metabolites are inactive, and only a small amount of fentanyl (8-10%) is renally and fecally cleared (McClain & Hug, 1980;Mather, 1983;Poklis, 1995).…”
Section: Traffickingmentioning
confidence: 99%
“…Like fentanyl and other fentanyl analogs, acetylfentanyl, acrylfentanyl, and 4-fluoro-isobutylfentanyl each have a major inactive nor-metabolite produced by N-dealkylation (Watanabe et al, 2017). In addition, each also has a hydroxyethyl and hydroxymethyoxy metabolite, similar to fentanyl.…”
Section: Fentanyl Analogsmentioning
confidence: 99%
See 2 more Smart Citations